Export-Orientation of Foreign Manufacturing Affiliates in India: Factors, Tendencies and Implications - Jaya Prakash PRADHAN; Keshab DAS; Mahua PAUL (Eurasian Journal of Business and Economics, 2011)
This paper addresses an important development issue in the literature of international production, namely, what motivates market-seeking foreign direct investment (FDI) to undertake export activities. It is well recognized in the concerned literature that export-oriented FDI is more beneficial for the host country than purely domestic market-seeking FDI. However, the existing literature has not examined those factors that could motivate existing market-seeking FDI into export activities. The present study addresses this issue and identifies factors encouraging market-seeking FDI to take up export activities. The empirical analysis of exportorientation of foreign firms in Indian manufacturing across 17 Indian industries during 1991–2005 has brought out several policy issues important for increasing export-orientation of foreign firms in a developing country like India.